2015
DOI: 10.1038/mp.2015.142
|View full text |Cite|
|
Sign up to set email alerts
|

Fluoxetine effects on molecular, cellular and behavioral endophenotypes of depression are driven by the living environment

Abstract: Selective serotonin reuptake inhibitors (SSRIs) represent the most common treatment for major depression. However, their efficacy is variable and incomplete. In order to elucidate the cause of such incomplete efficacy, we explored the hypothesis positing that SSRIs may not affect mood per se but, by enhancing neural plasticity, render the individual more susceptible to the influence of the environment. Consequently, SSRI administration in a favorable environment promotes a reduction of symptoms, whereas in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
134
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(148 citation statements)
references
References 81 publications
13
134
1
Order By: Relevance
“…The results concerning the neural and behavioral response to fluoxetine treatment displayed in the different environmental conditions by the experimental subjects used in this study have been published elsewhere (Alboni et al, 2016). These show that the exposure to 14 days of stress before treatment induced a depression-like phenotype and the neurobehavioral profile was affected by treatment according to the quality of the environment.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The results concerning the neural and behavioral response to fluoxetine treatment displayed in the different environmental conditions by the experimental subjects used in this study have been published elsewhere (Alboni et al, 2016). These show that the exposure to 14 days of stress before treatment induced a depression-like phenotype and the neurobehavioral profile was affected by treatment according to the quality of the environment.…”
Section: Introductionmentioning
confidence: 82%
“…It is worth noting that, in order to assess the effects of treatment in individuals showing a depression-like phenotype, we administered fluoxetine to mice previously exposed to chronic stress. Such pre-exposure activates the hypothalamic-pituitary-adrenal axis, increasing corticosterone levels (Alboni et al, 2016;Milior et al, 2015), and likely affects the interaction among the drug, the brain and immune system, making the results not applicable to different circumstances. However, this procedure has been chosen because it reproduces the clinical condition of patients who, before receiving the treatment, already show depressive symptoms and have high levels of cortisol (Juruena et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…106 Indeed, evidence suggests that environmental enrichment is necessary for the antidepressant-like effect of fluoxetine in mice, and that this effect is mediated through increased hippocampal BDNF and decreased corticosterone levels. 107 Increasing evidence supports a role for SSRIs in the enhancement of synaptic plasticity, 108 and repeated treatment in mice can reactivate cortical plasticity after monocular deprivation 109 and restore behavior in a fear extinction paradigm. 110 Likewise in humans, if administered early enough, chronic fluoxetine treatment can improve motor deficits in stroke patients.…”
Section: Antidepressants Alter Cellular Functioning Through Epigenementioning
confidence: 99%
“…Actually, repeated individual cross-over testing would be required to eliminate several sources of variance and determine the real response rate. Recently, it could be demonstrated that even in mice the response rate under treatment with selective serotonin reuptake inhibitors was significantly dependent on the circumstances of the environment 8 . In everyday practice, key predictors of the individual response rate are in fact the "health care system" and the variable "doctor" 7 .…”
mentioning
confidence: 99%